MUCINOUS CARCINOMA OF THE OVARY IN PERITONEAL FLUID - Prima Adelia Rachmita; Rachmadijah Zuryati Nizar; Yessy Setiawati (Journal Medical Universitas muhammadiyah Makassar, 2022)
Peritoneal cytology is crucial in the diagnosis and staging of abdominal and pelvic malignancies. Diagnostic pitfalls can be avoided by having an understanding of the different methods of sampling, a familiarity with cytomorphology of the various specimen types, adequate clinical history, and an ability to prepare cell blocks and/or review other prior or concurrent specimens. Ovarian cancer is the second most frequent type of gynecological malignancy but the most lethal. While high-grade serous carcinoma is the most common histological subtype, mucinous carcinoma of the ovary (MCO) was believed to constitute around 4% of ovarian malignancies. It is critical to diagnose these rare tumors correctly to ensure proper treatment, avoid mortality, and preserve fertility for young women.